Analisis Kinerja Keuangan Pada PT Asuransi Ramayana Tbk Dengan Pendekatan Cash Flow Untuk Tahun 2014-2017 - Julia T. Wahani; Tinneke M. Tumbel; Dantje Keles (JURNAL ADMINISTRASI BISNIS, 2019)
This study aims to determine the financial performance of PT Asuransi Ramayana Tbk by using a cash flow ratio analysis. The type of data used in this study is quantitative data. The data source used in this study is secondary data sources. The technique of collecting data using the documentation method is by retrieving data contained in the Indonesia Stock Exchange. The data analysis tool used is the Operating Cash Flow Ratio (AKO), Operating Cash Flow Ratio to Total Debt (AKOTH), Cash Flow Ratio to Capital Expenditures (AKOPM) and Cash Flow Ratio to Net Income (AKOLB). The results of this study indicate that the financial performance of PT Asuransi Ramayana Tbk. based on the 2014-2017 operating cash flow ratio is not good because it is below the value 1. So that insurance companies are unable to pay current and total debt obligations through operating cash flows, difficulty financing their capital expenditure through operating cash flows, and the possibility that the company has not been able to pay dividends to customers using operating cash flows. PT Asuransi Ramayana Tbk must increase company revenue and reduce excessive investment expenditure.